Quality of Drinking-water at Source and Point-of-consumption - Drinking Cup As a High Potential Recontamination Risk: A Field Study in Bolivia (Journal of Health, Population and Nutrition, 2010)
In-house contamination of drinking-water is a persistent problem in developing countries. This study aimed at identifying critical points of contamination and determining the extent of recontamination after water treatment. In total, 81 households were visited, and 347 water samples from their current sources of water, transport vessels, treated water, and drinking vessels were analyzed. The quality of water was assessed using Escherichia coli as an indicator for faecal contamination. The concentration of E. coli increased significantly from the water source [median=0 colony-forming unit (CFU)/100 mL, interquartile range (IQR: 0-13)] to the drinking cup (median=8 CFU/100 mL; IQR: 0-550; n=81, z=-3.7, p